Research progress on plant tolerance to soil salinity and alkalinity in sorghum - Rui-dong HUANG (Journal of Integrative Agriculture, 2018)
Sorghum is an important source of food, feed and raw material for brewing, and is expected to be a promising bioenergy crop. Sorghum is well known for its strong resistance to abiotic stress and wide adaptability, and salt tolerance is one of its main characteristics. Increasing sorghum planting acreage on saline-alkalien land is one way to effectively use this kind of marginal soil. In this paper, domestic and overseas research on plant tolerance to soil salinity and alkalinity in sorghum, including salt-tolerant genetics and breeding, physiology, cultivation, and identification of tolerant germplasms, are reviewed. Suggestions for further studies on salinity and alkalinity tolerance in sorghum are given, and the prospects for sorghum production in saline-alkalien land are discussed.